Treatment of hepatitis C in injecting drug users in the Perth metropolitan area - Rashidi, Amineh (Curtin University, 2016)
This study used a sequential exploratory mixed methods research to develop a better understanding of the context of treatment intentions of IDUs living with HCV in Perth Metropolitan area. Sixty three percent of participants expressed that they had intention to uptake HCV treatment. Characteristics of treatment, stigma and lack of support emerged as factors influencing intention to uptake HCV treatment. The findings will help to make the world a better place by scaling up HCV treatment for IDUs in the community setting.